PERAN MEDIASI STRES KERJA DALAM HUBUNGAN JOB INSECURITY DAN BEBAN KERJA TERHADAP TURNOVER INTENTION - Heni Susilowati; Widya Retno Ayuningsih (LPPM Politeknik Pratama, 2025)
Garment companies are faced with the challenge of employee turnover intention that has not been fully resolved. This study aims to examine the relationship between job insecurity and workload on employee turnover intention through the mediation role of work stress in the garment industry Mas Arya 2 Semarang. Questionnaires were collected from 96 samples of employee staff using proportional sampling techniques with the criteria of permanent employees in the production department who have worked for at least 6 months. Data analysis used partial least squares (SEM-PLS). The findings of the study explain that job insecurity and workload directly affect employee work stress and employee turnover intention. Work stress indirectly acts as a mediator that influences the relationship between job insecurity and workload on employee turnover intention.